2019
DOI: 10.1108/mbe-11-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

Mock-ups as a tool for assessing customer value early in the development process

Abstract: Purpose This paper aims to propose an approach to broaden the focus of a low-fidelity prototype (i.e. mock-up) to enable user experimentation in a real environment at the early stages of the product development process. The functionality approaching a real solution enables customers to experience the key functionality, and therefore, the perceived customer value of the new product idea before major investments in the development. Design/methodology/approach The study is based on an interventionist case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Customers seek concrete benefits from DTs. This observation can be confirmed by existing literature – the studies by Khalifa, (2004) and Lyly-Yrjänäinen et al (2019) also concluded that customers need to be convinced about the overall advantages of a solution that considerably exceeds any disadvantages to encourage customers to make a purchasing decision. Furthermore, there is an obvious need for more open arrangements and infrastructures for data sharing and shared goals among the actors involved in developing new DT-based businesses.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Customers seek concrete benefits from DTs. This observation can be confirmed by existing literature – the studies by Khalifa, (2004) and Lyly-Yrjänäinen et al (2019) also concluded that customers need to be convinced about the overall advantages of a solution that considerably exceeds any disadvantages to encourage customers to make a purchasing decision. Furthermore, there is an obvious need for more open arrangements and infrastructures for data sharing and shared goals among the actors involved in developing new DT-based businesses.…”
Section: Discussionsupporting
confidence: 63%
“…DTs may present problems also regarding data ownership and security issues (Fuller et al , 2020), collaboration models and openness between different actors (Fuller et al , 2020; Meierhofer et al , 2020), and with the creation of novel customer value and business models (Camposano et al , 2021; Olaf and Hanser, 2019). Moreover, the gains of acquiring or using a solution must exceed its related pains, such as the needed resources and costs, and convincing customers of these benefits before the purchasing decision can be challenging (Khalifa, 2004; Lyly-Yrjänäinen et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that the best instructional media in learning Mount Merapi Eruption was mockup. Mock up is a prototype using affordable and easly to find materials [8]. On the other hand, the most effective instructional media to learn about earthquake is poster.…”
Section: Instructional Strategies For Landslidementioning
confidence: 99%